2014
DOI: 10.1016/j.jad.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-related proteins and proliferation markers in the orbitofrontal cortex in major depressive disorder

Abstract: Background: In major depressive disorder (MDD), lowered neural activity and significant reductions of markers of cell resiliency to degeneration occur in the prefrontal cortex (PFC). It is still unclear whether changes in other relevant markers of cell vulnerability to degeneration and markers of cell proliferation are associated with MDD. Methods: Levels of caspase 8 (C8), X-linked inhibitor of apoptosis protein (XIAP), direct IAP binding protein with low pI (DIABLO), proliferating cell nuclear antigen (PCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…However, these markers were significantly decreased in alcohol dependent subjects with comorbid major depression (Miguel-Hidalgo et al, 2010). In contrast, recently we found that there was a very significant decrease in the levels of connexin 43, the main gap junction forming protein in astrocytes, and in Cx43-immunoreactive gap junctions aggregates in alcohol dependent subjects regardless of the presence of depression (Miguel-Hidalgo et al, 2014). …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, these markers were significantly decreased in alcohol dependent subjects with comorbid major depression (Miguel-Hidalgo et al, 2010). In contrast, recently we found that there was a very significant decrease in the levels of connexin 43, the main gap junction forming protein in astrocytes, and in Cx43-immunoreactive gap junctions aggregates in alcohol dependent subjects regardless of the presence of depression (Miguel-Hidalgo et al, 2014). …”
Section: Discussionmentioning
confidence: 72%
“…We have recently found that in major depressive disorder (without comorbid alcoholism) there is an age-related increase in PCNA levels as compared to non-psychiatric control subjects (Miguel-Hidalgo et al, 2014) even if these subjects diagnosed with only depression had significantly lower density of Ki-67-immunoreactive cells. Thus, increased PCNA levels may signal not only direct alcohol effects on cellular function, but also altered neural activity patterns.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The protocol included obtaining written consent from next-of-kin for retrospective interviews to compile relevant diagnostic information according to procedures detailed in previous publications (Miguel-Hidalgo et al, 2014; Whittom et al, 2014). Blocks of postmortem tissue were collected during autopsy at the Cuyahoga County Medical Examiner’s Office, Cleveland, Ohio.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of hippocampal neurons is found in some depressed individuals and correlates with impaired memory and dysthymic mood (Sheline et al, 2003). Many other signaling pathways have also been reported to play important roles in the pathogenesis of MDD, such as hypothalamic-pituitary-adrenal (HPA)-axis, inflammatory pathways (Martin et al, 2015), the mammalian target of rapamycin (mTOR) signaling pathway (Jia and Le, 2015;Jernigan et al, 2011), and the extracellular signal-regulated kinase/ CREB/BDNF pathway (Wang et al, 2013), apoptosis (Miguel-Hidalgo et al, 2014), autophagy (Jia and Le, 2015;Gassen et al, 2015) and so on (for review, see (Chaudhury et al, 2015;Menard et al, 2015)). These evidences support the hypothesis that risk factors, which disrupt neuronal function and morphology resulting in dysfunction of the neural circuitry underlying the mood regulation and cognitive function through converging molecular and cellular mechanisms, may all contribute to the pathophysiology of MDD and are potential targets of antidepressants.…”
Section: The Risk Factors Of Depressionmentioning
confidence: 99%